Mapping Collaborative Governance Strategies for Regional Health Policy Sustainability: A Systematic Review Based on Socioeconomic Data Integration in Pursuit of Universal Health Coverage in Gorontalo - Afriyani Katili; Asna Aneta; Yanti Aneta (Departemen Administrasi Publik, Universitas Diponegoro, 2026)
This study aims to systematically review the implementation of collaborative governance strategies in regional health policy, with a particular focus on integrating socioeconomic data to support Universal Health Coverage (UHC). The province of Gorontalo, Indonesia, is highlighted as a reflective case of underrepresented contexts in global health governance literature.A systematic literature review (SLR) was conducted following the PRISMA 2020 protocol. Forty-five peer-reviewed articles published between 2000 and 2025 were identified through Scopus, PubMed, ScienceDirect, and Google Scholar. Inclusion criteria emphasize empirical studies on regional health governance, socioeconomic data utilization, and multi-actor collaboration. Data were analyzed using thematic synthesis (Thomas & Harden, 2008), supported by coding reliability checks and the CASP qualitative appraisal tool to ensure rigor and validity.The analysis revealed three dominant themes: actor fragmentation and mandate asymmetry, partial integration of socioeconomic data into decision-making, and facilitative leadership as a critical success factor. While Latin America demonstrated advanced data integration supported by strong regulation, Southeast Asia and Sub-Saharan Africa demonstrated collaborative practices rooted in trust-building but hindered by limited institutional interoperability. In Gorontalo, strategies remain experimental, relying heavily on health-sector data while neglecting poverty, education, and demographic indicators. This highlights the absence of a comprehensive framework bridging local data ecosystems with collaborative policy design.This review identifies a persistent gap in data-integrated collaborative governance within regional health policy, particularly in marginalized contexts. The study proposes the Integrated Collaborative Governance Framework for UHC Realization, emphasizing trust-building, leadership, and local cultural values (eg, huyula) as essential drivers. The findings enrich collaborative governance theory while offering practical insights for strengthening UHC-oriented health policies in Indonesia and the Global South.